بحث استطلاعي لآراء عينة من المدراء العاملين في شركتي زين وآسيا سيل - Leila Mohsen Hassan al-Hakim (Iraqi Journal for Administrative Sciences, 2024)
The research aims to explore the impact of event marketing on customer perceptions of service quality. In the sense of demonstrating the possibility of using the marketing mechanisms of the event to achieve positive perceptions of the quality of services to customers, and the extent of adoption by organizations investigating the concept of marketing the event in its dimensions and mechanisms and its applicability. Therefore, the research started from a problem expressed by a number of intellectual and applied questions, The aim of the answer is to explore the intellectual implications of the variables that the study has discussed (event marketing - customer perceptions of the quality of services) And then identify the level of importance, impact and applicability in the Iraqi communications companies. The research was applied to the communication companies in Iraq (Zain and Asia Cell), The sample analyzed (65) from different functional levels and for the purpose of data collection, the research relied on the questionnaire as a main tool prepared in the light of reliable and reliable standards in a good environment of choice as well as the opinions and ideas of researchers specialized in the field of research variables after Translated from English to Arabic, After the questionnaire data were unloaded, a set of statistics were used in the SPSS package as correlation and regression factors, and in light of statistical analysis outputs, The results showed a statistically significant relationship between the variables of the research. In the light of the results, a number of conclusions were drawn: The results of the hypothesis analysis indicate that the change in the level of availability of the event marketing is reflected in the change in the quality of services. Based on the conclusions reached, a number of recommendations have been derived. These included the need for the management of the communication companies to adopt the philosophies and methods of event marketing, The quality of its services provided and work to strengthen them